Efektivitas Model Problem Based Learning terhadap Hasil Belajar Materi Front Wheel Alignment pada Kendaraan Ringan di SMK - Chrisnadivanda, Alta Hizkia; Noor, Ridwan Adam Muhamad; Ramdhani, Ramdhani (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to analyze the effectiveness of the Problem Based Learning (PBL) model on student learning outcomes in the Front Wheel Alignment material for light vehicles in Vocational High Schools. The study used a quantitative approach with a quasi-experimental method and nonequivalent control group design. The study involved class XI TKR-3 as an experimental class with the PBL model and class XI TKR-1 as a control class with the Inquiry Learning model. Data were collected through pretests and posttests as well as observations of the implementation of learning. Data analysis included validity, reliability, normality, homogeneity, Paired Samples t-test, Independent Samples t-test, and N-Gain tests. The results showed that the implementation of PBL was carried out according to the learning syntax. The results of the Paired Samples t-test showed a significant difference between the pretest and posttest scores in both classes with a significance value of <0.001. The N-Gain value of the experimental class was 0.80, which is included in the high category, while the control class was 0.40, which is included in the medium category. The Independent Samples t-test results showed a significance value of 0.000 < 0.05, indicating a difference in learning outcomes between the experimental and control classes. Thus, PBL effectively improved student learning outcomes in Front Wheel Alignment compared to Inquiry Learning.